2015
DOI: 10.1208/s12248-015-9798-5
|View full text |Cite
|
Sign up to set email alerts
|

A Neutralizing Antibody Assay Based on a Reporter of Antibody-Dependent Cell-Mediated Cytotoxicity

Abstract: Abstract. Benralizumab is a humanized anti-IL5 receptor α (IL5Rα) monoclonal antibody (mAb) with enhanced (afucosylation) antibody-dependent cell-mediated cytotoxicity (ADCC) function. An ADCC reporter cell-based neutralizing antibody (NAb) assay was developed and characterized to detect NAb against benralizumab in human serum to support the clinical development of benralizumab. The optimal ratio of target cells to effector cells was 3:1. Neither parental benralizumab (fucosylated) nor benralizumab Fab resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…3 Chimeric 2E2 IgG 1 (c2E2 IgG 1 ) is a chimeric afucosylated IgG 1 antibody with the same specificity as c2E2 IgG 4 that is anticipated to enhance antibody-dependent cellular cytotoxicity (ADCC) through natural killer (NK) cell engagement of CD16, as described with benralizumab, an afucosylated IgG 1 anti-IL-5 receptor antibody approved for the treatment of asthma. 8,9 Although prior studies in small numbers of NDs and patients with HESs have demonstrated Siglec-8 expression on peripheral blood eosinophils 10 and detected soluble Siglec-8 (sSiglec-8) in sera from some patients with HESs, 11 little is known about the variability and regulation of Siglec-8 expression in vivo. A weak correlation was noted between serum sSiglec-8 levels and absolute eosinophil counts (AECs).…”
mentioning
confidence: 99%
“…3 Chimeric 2E2 IgG 1 (c2E2 IgG 1 ) is a chimeric afucosylated IgG 1 antibody with the same specificity as c2E2 IgG 4 that is anticipated to enhance antibody-dependent cellular cytotoxicity (ADCC) through natural killer (NK) cell engagement of CD16, as described with benralizumab, an afucosylated IgG 1 anti-IL-5 receptor antibody approved for the treatment of asthma. 8,9 Although prior studies in small numbers of NDs and patients with HESs have demonstrated Siglec-8 expression on peripheral blood eosinophils 10 and detected soluble Siglec-8 (sSiglec-8) in sera from some patients with HESs, 11 little is known about the variability and regulation of Siglec-8 expression in vivo. A weak correlation was noted between serum sSiglec-8 levels and absolute eosinophil counts (AECs).…”
mentioning
confidence: 99%
“…Methods for quality control preparation, screening cutoff determination, sensitivity, drug tolerance, selectivity, cell culture, and assay procedures for the ADCC cell-based NAb assay have been described in detail (15). In brief, the validated CBA is an ADCC assay that consists of target cells (a murine cytotoxic cell line CTLL-2 stably transfected with human IL-5R) and an effector cell line (human NK92 cells).…”
Section: Cba Methodsmentioning
confidence: 99%
“…For the CLBA, the concentrations of the polyclonal anti-benralizumab idiotype antibody were 2.0, 1.5, 1.0, 0.75, 0.5, 0.25, 0.1, 0.05, 0.025, 0.0125, and 0 μg/mL; and the benralizumab concentrations were 1.0, 0.5, 0.25, 0.1, 0.05, 0.025, and 0 μg/mL. For the CBA, the concentrations of the polyclonal anti-benralizumab idiotype antibodies were 10, 5, 2.5, 1.25, 0.63, 0.31, and 0 μg/mL, and the benralizumab concentrations were 12.5, 6.25, 3.13, 1.56, 0.78, 0.39, and 0 μg/mL (15). For the binding ADA assay, the concentrations of the polyclonal anti-benralizumab idiotype antibody were 4.0, 2.0, 1.0, 0.5, 0.25, and 0 μg/mL, and the benralizumab concentrations were 500, 250, 100, 50, 25, and 0 μg/mL.…”
Section: Drug Tolerance Level Determinationmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonspecific matrix interference in a cell-based NAb assay can be a limitation and can often be eliminated by sample dilution, provided that the assay sensitivity and drug tolerance limit are not adversely impacted. In a cell-based NAb assay, either the drug target (soluble shed receptor) or a competitive antagonist to the drug (ligand) may be present as potential specific interfering factors [33].…”
Section: Nab Assaysmentioning
confidence: 99%